The US-Russian spheres of influence in the post cold war era / Albana Reci - Albana , Reci (2016)
This study is an assessment of the US-Russian spheres of influence strategy in the post-Cold War. The research framework offers an examination of the conceptual and practical aspects of sphere-of-influence. An analysis of NATO-Warsaw Pact is used to connect the historical and contemporary US-USSR/Russian pursuit for influence projection. The central argument of this study is that sphere-of-influence remains a strategic frame forever present in the foreign policies and geopolitical visions of the major powers. Both these powers are increasingly important within their relevant sphere of influence and both aim an influence projection beyond their spheres. Though unequal, one is a global power, the other a regional power, the two countries are capable of leading and framing the political, economic and security problems in their respective spheres. This study has chosen three contemporary evidences because they represent incompatible geopolitical positions between the US and Russia, which are the NATO’s expansion and its open-door policy towards the CIS region, the recent Ukrainian Revolution and Syrian crisis. The sources available to conduct this research came from a collection of archival documents, official papers, and transcripts, speeches of leading figures of all the parties involved in the three events. Such data collection contributed to the argumentative aspect of this study with sufficient proof and academic evidence. The structure of the study is presented in two parts: the first part examines the concept of the sphere of influence and the US-USSR' spheres of influence during the Cold War; the second part is an assessment of the continuity for spheres of influence by the US and Russia in the post-Cold War. Many have offered significant findings about the US-Russian relations in the historical and contemporary scholarly climate. The main findings resulting from this study are: throughout the Cold War and post-Cold War period, both the US and Russia have been equally determined to maintain control over the events that affect the status of their spheres of influence. Secondly, in terms of sphere of influence, the Ukrainian Revolution is significant and strategic for the US-Russian geopolitics as was the status of the divided Germany during the Cold War. The fact that Germany was critical for the influence over Europe and Ukraine and is also crucial for influence over the CIS region. Thirdly, NATO’s open-door policy to the CIS countries triggers not only a more assertive Russia but also a more aggressive Russia. Fourthly, Syria has become a critical situation in the Middle East for all the regional and international players involved because it is the only Middle Eastern case where both US and Russia are involved and standing on the opposite sides. Lastly, while the three evidences being discussed in this research are ongoing events that still needs to be watched and reflected upon, the US’ and Russia’s pursuit for influence projection remains. Between the US and Russia, whether mutually assured security frame or the sphere of influence approach is employed, it has always has been about who gains a strong and significant political posture in world affairs.